2011
DOI: 10.1371/journal.pone.0025322
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorders and Schizophrenia: Meta-Analysis of the Neural Correlates of Social Cognition

Abstract: ContextImpaired social cognition is a cardinal feature of Autism Spectrum Disorders (ASD) and Schizophrenia (SZ). However, the functional neuroanatomy of social cognition in either disorder remains unclear due to variability in primary literature. Additionally, it is not known whether deficits in ASD and SZ arise from similar or disease-specific disruption of the social cognition network.ObjectiveTo identify regions most robustly implicated in social cognition processing in SZ and ASD.Data SourcesSystematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
218
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(245 citation statements)
references
References 96 publications
16
218
0
11
Order By: Relevance
“…Most of the regions in which we found gray matter reductions have consistently been implicated in socio-emotional processing and communication abilities that are deficient in ASD, such as (i) theory of mind (Di Martino et al 2009;Van Overwalle, 2009;Sugranyes et al 2011), (ii) mirror neuron functioning and language (Lai et al 2012;Molenberghs et al 2012), and (iii) limbic system functions (Sugranyes et al 2011). However, some of the aforementioned regions have also been associated with functions other than social ones.…”
Section: Regional Gray Matter Abnormalities and Their Correlation Witmentioning
confidence: 52%
“…Most of the regions in which we found gray matter reductions have consistently been implicated in socio-emotional processing and communication abilities that are deficient in ASD, such as (i) theory of mind (Di Martino et al 2009;Van Overwalle, 2009;Sugranyes et al 2011), (ii) mirror neuron functioning and language (Lai et al 2012;Molenberghs et al 2012), and (iii) limbic system functions (Sugranyes et al 2011). However, some of the aforementioned regions have also been associated with functions other than social ones.…”
Section: Regional Gray Matter Abnormalities and Their Correlation Witmentioning
confidence: 52%
“…Schizophrenia is characterized by grave impairments in WM (52) that are associated with reduced dlPFC activity and thought disorder (53). Reductions in dlPFC activity are also associated with dysregulated behavior and attention in mania (54) and ADHD (55), especially in the right hemisphere, whereas dorsomedial PFC hypoactivity is associated with social deficits in both schizophrenia and autism (56). PFC deficits are also a component of dementias such as AD, where there is early accumulation of β-amyloid and phosphorylated tau early in the disease, including tangles in layer III pyramidal cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a crucial implication of this study is to show that social neuroscience can be used among ADS to develop innovative theoretical and therapeutic perspectives. Neural correlates of social cognition have recently been explored in schizophrenia and autism (Sugranyes et al, 2011), and we underlined the interest of applying social neuroscience paradigms to alcohol-dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The omnipresence of social impairments among neurological and psychiatric populations recently led social neuroscience to expand towards pathological states (Adolphs, 2010). The first clinical studies gave promising results, describing abnormal cortical and limbic activations during interpersonal processing in schizophrenia, depression, and autism (Sugranyes et al, 2011). Nevertheless, social exclusion has up to now only been explored in autism, where two studies showed reduced insula and dorsal anterior cingulate cortex (dACC) activations during ostracism (Bolling et al, 2011;Masten et al, 2011).…”
Section: Introductionmentioning
confidence: 99%